Outcome and evaluation of prognostic factors after pancreaticoduodenectomy for distal cholangiocarcinoma - Byrling, Johannes (Ann Gastroenterol, 2017)
BACKGROUND: The aim of the present study was to examine the outcomes and prognostic factors after surgery with curative intent for distal cholangiocarcinoma during a modern timespan, in a Swedish tertiary referral center. METHODS: All patients who underwent pancreaticoduodenectomy for distal cholangiocarcinoma between April 2008 and December 2015 were identified. Survival was estimated using the Kaplan-Meier analysis. Demographic, clinical, laboratory and histopathological data were evaluated for prognostic factors relating to mortality, using univariable and multivariable statistical analysis. RESULTS: Fifty-four patients were included. The mean age was 68±8 years and 21 (39%) of the patients were female. Jaundice was present at diagnosis in 73% of the patients. There was no 90-day mortality. Complications graded as Clavien-Dindo ≥3 occurred in 10 (19%) of the patients. Twenty-eight (52%) received adjuvant therapy. Overall survival rates at 1, 3, and 5 years were 80%, 21%, and 9.2%, respectively. Median survival was 22.2 months. The presence of lymph node metastases was found to be the only independent predictor of survival (hazard ratio 2.88, 95% confidence interval 1.22-6.84; P=0.016). The total number of lymph node metastases, lymph node ratio or total number of resected nodes did not improve the prediction. CONCLUSIONS: We found that the recurrence rate was higher and the survival poorer after surgery for distal cholangiocarcinoma than has previously been reported. Lymph node status at the time of resection was the most important prognostic factor for survival in the current material.